Pradyumna - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel depicts Varuna, a Vedic deity. Varuna is the God of oceans and also a dikpala (guardian of directions). He is the guardian of the west, hence his image is placed on the west face of the adhisthana. Varuna is seated in a lalitasana posture on its mount, the mythical sea creature called makara. In his left hand, Varuna is holding the Gandiva, a divine bow which was gifted by Varuna to Arjuna in the Mahabharata. He is surrounded by four female attendants. Two attendants in the foreground are seated on circular seats and two in the background are standing. The seated lady on the left is holding an arrow. The seated lady on the right has long braided hair. The faces, feet, and hands of the figures are broken and their attributes are not clear.